Treatment of osteoarthritis and other hip arthropathies: current status - Nin Vivo, Esteban; Silveri, Asdrúbal (Cirugía del Uruguay, 1973)
The authors refer to total prothetic replacement of thigs. The four fundamental principles in prothetic replacements of any joint, and thigh in particular, are discussed. They are: 1) use of inert materials; 2) satisfactory mechanic design of prothesis; 3) attachment of prothesis to live bone, 4) surgical technique employed. Reference is made to postoperatory period -mediate and immediate- listing sone principles for rehabilitation of patients thus treated.